Antioxidant Activities of Various Fraction Levels of Kaik Kaik (Uruparia Multiflora K.Schum. & Lauterb): indonesia - Hadi, Samsul; Setiawan, Deni; Nastiti, Kunti (Tropical Biopharmaca Research Center, IPB University, 2024)
Borneo has abundant biodiversity, especially regarding medicinal plants. One of the plants used in traditional medicine by the Dayak tribe in Kalimantan is kaik-kaik (Uncaria cordata (Lour.) Merr.), so research is needed to evaluate the activity of this plant. One of the methods used to assess its medicinal properties is through its antioxidant activity. This research aimed to test the antioxidant activity of various fractions derived from U. cordata stems. The study began with ethanol extraction followed by fractionation using n-hexane, ethyl acetate, and distilled water. The extracts and fractions obtained were then tested for antioxidant activity using the DPPH radical capture method. The results indicated that the n-hexane fraction, with a yield of 0.69%, contains terpenoids/steroids, alkaloids, and flavonoids; the ethyl acetate fraction, with a yield of 1.453%, contains alkaloids and flavonoids; and the distilled water fraction, with a yield of 4.832%, contains saponins, tannins, alkaloids, phenols, and flavonoids. The n-hexane, ethyl acetate, and distilled water fractions exhibited antioxidant capacity with IC₅₀ values of 138.39 ± 0.3777 ppm, 48.51 ± 0.056 ppm, and 36.31 ± 0.111 ppm, respectively. This research concluded that the distilled water fraction was the most active and is classified as a very strong antioxidant.